Hello Mr Twiddle! - Blyton, Enid; Dell, Stephen (London Bounty Books, 2014)
The story of Mr Twiddle, who is always doing something silly such as putting fireworks on the fire by mistake, trying to read the herrings and feeding the newspaper to the cat. He just can't remember anything.
Keywords: English-Fiction